Soil biological quality in rhizosphere, growth, and yield of upland rice grown on acid soil after amended biochar enriched sap of Kappaphycus alvarezii - TRESJIA CORINA RAKIAN; LAODE MUHAMMAD HARJONI KILOWASID; LA ODE AFA; ARDISTA RISKYANA; NURAZIZAH NURAZIZAH; YUSLITA WIJAYANTI; ANDI BAHRUN; IMRAN SUBAIR; NINI MILA RAHNI; SYAMSU ALAM; SARAWA SARAWA; LA KARIMUNA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Rakian TC, Kilowasid LMH, Afa LO, Riskyana A, Nurazizah, Wijayanti Y, Bahrun A, Subair I, Rahni NM, Alam S, Sarawa, Karimuna L. 2023. Soil biological quality in rhizosphere, growth, and yield of upland rice grown on acid soil after amended biochar enriched sap of Kappaphycus alvarezii. Biodiversitas 24: 6780-6792. Biological soil quality is essential in evaluating soil management practices using biochar enriched for upland rice growth on acid soil. Therefore, the study aimed to (i) analyze the effect of biochar-enriched sap of Kappaphycus alvarezii (K-sap) on the abundance of Arbuscular Mycorrhizae Fungi (AMF), bacteria, and protozoa in rhizosphere soil, growth, and yield of upland rice, and (ii) the relationship between the abundance of soil biota and the growth and yield components, as well as straw N, P, and K content on acid soil. Four upland rice were grown on acid soil incubated with biochar-enriched sap for two weeks in pots. Nine treatments of the biochar-enriched sap were tested, namely control, 5% biochar-0% K-sap, 5% biochar-5% K-sap, 5% biochar -10% K-sap, 5% biochar-15% K-sap, 7.5% biochar-0% K-sap, 7.5% biochar-5% K-sap, 7.5% biochar-10% K-sap, and 7.5% biochar-15% K-sap. Each treatment was three replicates in a randomized block design. The results demonstrated that the AMF spores quantity decreased while flagellates increased in the soil rhizosphere. The P and K content increased, the N:P decreased, and P:K ratio varied in the straw of the upland rice. Plant height and total spikelets increased, while root dry weight and roots to shoots ratio (R:S) decreased with biochar enriched. The abundance of AMF spores and flagellates correlated positively and negatively with R:S. Furthermore, R:S was negatively correlated with plant height and total spikelets. Plant height and total spikelets showed a positive correlation, while root dry weight and R:S was negatively correlated with K content in shoot tissue. The P and K contents with N:P ratio and N:P with P:K were negatively correlated. In conclusion, biochar-enriched K-sap effectively regulated the activity and composition of soil biota in the rhizosphere, influencing upland rice's growth, yield, and nutrient balance uptake on acid soils.